KECERMATAN SISWA MENGAMATI KATA KUNCI PADA SOAL CERITA MATERI PERBANDINGAN BERBALIK NILAI - Meliyana Raharjanti; Toto Nusantara; Sri Mulyati (Pascasarjana Universitas Negeri Malang, 2016)
The student's observation of the problem needs to be careful. More careful in the observation, more complete information obtained in solving the problems. This article describes about student's observation precision of keywords in the given word problems about inverse proportion. The study involved 14 boys and 18 girls'students of 7th grade. Method of data collecting are test and interview. This study shows that only some of the keywords, i.e four of the seven key words, which is observed by the students. Most other keywords not identified by the students. This indicates that students are less careful in observing the keyword in problems. Ineffectiveness the choosen keywords by students have resulted that students indicated experiencing interference. Semakin cermat siswa mengamati soal, maka semakin lengkap informasi untuk menyelesaikan soal. Artikel ini mendeskripsikan kecermatan siswa mengamati kata kunci pada soal cerita materi perbandingan berbalik nilai. Penelitian ini melibatkan 14 siswa laki - laki dan 18 siswa perempuan kelas 7. Teknik pengumpulan data yang digunakan adalah tes dan wawancara. Penelitian ini menunjukkan bahwa hanya sebagian kata kunci, yaitu empat dari tujuh kata kunci, yang dicermati oleh siswa. Sebagian kata kunci lain tidak teridentifikasi oleh siswa. Hal ini mengindikasikan bahwa siswa kurang cermat dalam mengamati kata kunci pada soal. Ketidakefektifan kata kunci yang siswa pilih ini mengakibatkan siswa terindikasi mengalami interferensi.